UNIVERSITY NOTES. (The Accounting Review, 1927)
Abstract The article provides information about latest developments in the accounting department of various universities and colleges in the U.S., as of June 1927. H.H. Chapman, associate professor of accounting in the University of Alabama, will be on leave of absence for the year 1927-28. Chapman will hold a fellowship at Columbia University , where he will complete his graduate work. Chester H. Knight has been promoted to assistant professor of accounting and will have charge of the accounting work during Chapman's absence. Professor W.A. Berridge of Rhode Island-based Brown University leaves the department to go with the Metropolitan Life Insurance Co. as economist. A. F. Hinrichs will take charge of instruction in statistics and direct research activities of the Brown Bureau of Business Research. G. K. Bigge comes from the University of Michigan as assistant professor of economics in charge of the work in labor and business administration. Thomas L. Norton, instructor in economies, leaves to continue his studies at Columbia University.